THE INFLUENCE OF SOCIAL MEDIA CONTENT, PRODUCT QUALITY AND SERVICE QUALITY ON PURCHASE DECISIONS GRAPE SEEDS IN JOGJA ANGGUR GRAPE FARM - Ricky Apriadi; Kussudyarsana Kussudyarsana (Komitmen: Jurnal Ilmiah Manajemen, 2023)
This research aims to determine the influence of Social Media Content, Product Quality and Service Quality on the Decision to Purchase Grape Seeds at the Jogja Wine Grape Farm. The population in this study were all consumers who bought grape seeds at the Jogja Wine Grape Farm. The number of samples in this research was 100 respondents. The sampling used in this research was non-probability sampling using a convenience sampling approach. The data collection method uses a questionnaire. The data analysis technique for this research uses multiple linear regression analysis tests. The results of this research show that partially there is a significant influence of social media content, product quality and service quality on the decision to purchase grape seeds at the Jogja Wine Grape Farm. Simultaneously, there is a significant influence between the variables of social media content, product quality and service quality on the decision to purchase grape seeds at the Jogja Wine Grape Farm.